The Effect of Enforcement Of Mayor Regulation No. 888 Of 2012 On Street Vendors' Compliance (PKL) In Bandung Kulon District - Dewi, Yunita Fourina; Susilawati, Susilawati; Saputra, Ginanjar Wira (Doctoral Program of Social Science Pasundan University, 2024)
This study aims to examine the Effect of Enforcement of Major Regulation No. 888 of 2012 on Compliance with Street Vendors (PKL). The research method used a descriptive method with a quantitative approach, while the data collection technique was carried out by distributing questionnaires to several samples. The sample used was 85 people. From the results of the respondent's response variable (X) obtained a score of 3272 while variable (Y) obtained a score of 4608 from the results of the hypothesis test t_count 7.347 and t_table 1.988 then t_count> t_table so that Ho is rejected and Ha is accepted, which means the Enforcement of Major Regulation No. 888 of 2012 has an effect Against the Compliance of Street Vendors (PKL). Based on the coefficient of determination (KD), it is known that the achievement of the ability of the X variable affects the Y variable, namely 39.44%, while the remaining 60.56% is influenced by other variables that are not included. Suggestions in this study, especially Satpol PP personnel who apply regulations can be friendly and not arrogant in terms of taking action or imposing sanctions for street vendors who violate and are stubborn but be cooperative and it is also hoped that street vendors can follow the rules applied so that the beauty of the city of Bandung is maintained.